Fabrication of polyaniline/activated carbon composite and its testing for methyl orange removal: Optimization, equilibrium, isotherm and kinetic study. (August 2019) - Hasan, Mudassir; Rashid, Md Mamoon; Hossain, Muhammad M.; Al Mesfer, Mohammed K.; Arshad, Muhammad; Danish, Mohd; Lee, Moonyong; El Jery, Atef; Kumar, Narendra
Abstract: Polyaniline/Activated carbon composite was synthesized using in-situ oxidative chemical polymerization technique. The optimized composite (POAC) was applied for the removal of methyl orange (MO) from aqueous solution. Several studies such as changing the concentration of MO solution, contact time and adsorbent dosage were performed batch wise at optimum pH of 6.5. Within 2 h of the experiment 70% of MO was removed. A maximum monolayer adsorption capacity Q of 285 (mg/g) was obtained with Langmuir isotherm model. Pseudo second-order kinetic model explained the experimental data better than Pseudo-first order model and intra particle diffusion model. Saturation concentration of 62.92 (mg/L) obtained by utilizing Brunauer–Emmett–Teller (BET) parameters matched well with the assumed value 63 (mg/L). this work demonstrates that POAC is a potential and effective adsorbent. Graphical abstract: Image 1 Highlights: PANI/activated carbon composite material was fabricated. The composite was optimized to be used as an adsorbent for Dye removal. Several isotherms and kinetic models were fitted with the equilibrium data. The dye removal performance of composite material was observed to be excellent.